Cloning and mutational analysis of the fimb promoters in uropahogenic escherichia coli - Reuter, Brandon M. (My University, 2012)
Uropathogenic Escherichia coli (UPEC) cause an estimated 7 million urinary tract infections annually in the U.S. Type I pili, expressed by UPEC, are largely responsible for mediating bacterial attachment to host bladder cells. The jimB gene encodes a sitespecific recombinase that controls the orientation of an invertible DNA segment containing the promoter for the pilus structural gene.fimA. Three promoters have been mapped forjimB, but little is known about their respective function or hierarchy. In this study, jimB promoter mutants were created and used to establish ajimB promoter hierarchy while substantiating the influence two regulatory proteins, OmpR and GadE, have on type I pilus expression andjimB transcription. The UPEC strain UTI189 /::,.fimB was transformed with plasmids containing the jimB promoter mutants. Since pH and osmolality are known to affect type I pilus expression, transformed /::,.fimB cells were grown in Luria-Bertani broth pH 5.5 and 7.0 with or without 400 mM NaCI. Variation in surface piliation was determined by hemagglutination while variation injimB transcription was measured by quantitative reverse-transcriptase PCR. Hemagglutination analysis indentified nucleotides that may be important for the interaction of OmpR witl1 jimB promoter two, but failed to indentizy a region in which GadE interacts withjimB. Additional experiments are needed to clarifY these findings.
Keywords: Cloning; Escherichia coli infections.